The Effect of A Combination of Prenatal Yoga, Relaxation Music, and Agarwood Aromatherapy on Anxiety of Pregnant Women in the Third Trimester - Aprilia Kharisma Yogi; Ika Yulianti; Rusmiati Rusmiati; Rahmi Padlilah; Doris Noviani (Indonesian Journal of Global Health Research, 2024)
Anxiety disorders in pregnant women are associated with risks such as placental abruption, low birth weight, delayed motor and mental development of the fetus, and premature birth if not properly managed and prolonged. Anxiety in third-trimester pregnancy can be minimized using non-pharmacological interventions such as prenatal yoga, relaxation music, and aromatherapy. This study aimed to determine the effect of a combination of prenatal yoga, relaxation music, and agarwood aromatherapy on anxiety in third-trimester pregnant women at Karang Rejo Health Center. This quantitative study uses a quasi-experimental design without a control group and uses pretest and post-test measurements. The intervention group received a combination of prenatal yoga, relaxation music, and agarwood aromatherapy. Purposive sampling was used following inclusion criteria, with a total of 25 respondents. Data collection was conducted using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis was performed using univariate and bivariate analyses with the non-parametric Wilcoxon test. The results showed that the anxiety levels of third-trimester pregnant women before and after the intervention had a P value of 0.000 (P value < 0.005). This indicates that the combination of prenatal yoga, relaxation music, and agarwood/ Gaharu aromatherapy can be an effective alternative for reducing anxiety in third-trimester pregnant women.